Faculty verbal messages: scale development and initial validation - Violanti, Michelle T.; Garland, Michelle E. (Frontiers in Education, 2024)
Introduction This study set out to create a scale of messages faculty use when communicating with students and provide initial validation evidence for that scale. Methods Three studies were used to create and initially validate the scale. Study one used focus groups to have students generate a list of 65 messages. Study 2, a survey with exploratory factor analysis, yielded two factors: affirming (items) and disconfirming (items) messages. Study 3 confirmed the factor structure and provided initial construct validation based upon the relationship between messages and relational distance, motives to communicate, learner empowerment, and student motivation. Results Withdrawal mediates the relationship between faculty verbal messages and learner empowerment. Faculty verbal messages directly, without mediation, predict student motivation. Discussion Faculty verbal messages matter inside and outside the classroom. Both affirming and discomfiting messages can have a positive effect on students’ learning/motivation as well as the instructor-student relationship.